A prospective study on the incidence of rheumatoid arthritis among people with persistent increase of rheumatoid factor. Issue 2 (1st February 2000) - Halldórsdóttir, H D; Jónsson, T; Thorsteinsson, J; Valdimarsson, H
Abstract : OBJECTIVES: To study the stability of rheumatoid factor (RF) increases and to compare the incidence of rheumatoid arthritis (RA) in people with transient or persistent increase of one or more RF isotypes. METHODS: From an original cohort of nearly 14 000 participants in a population study, 135 previously RF positive persons were recruited in 1996 and evaluated according to the 1987 ACR criteria. The observation time ranged from 9–22 years (mean 16.5). Blood samples were obtained from all participants at entry and again in 1996. RESULTS: About 40% of the participants who had only one raised RF isotype in the original sample had become RF negative in 1996 compared with only 15% of those with increase of two or three RF isotypes (p=0.002). The seven participants who developed RA during the study period all had persistently raised RF. Six of the 54 participants with more than one RF isotype raised in 1996 developed RA, corresponding to an annual incidence of 0.67%, which was 7.5 times higher than observed in the other participants (p=0.045). CONCLUSION: Symptom free persons with persistently raised RF have greatly increased risk of developing RA. This suggests that dysregulation of RF production is a predisposing factor in RA.